Imaging multiple microRNAs in living cells using ATP self-powered strand-displacement cascade amplification - Meng, Xiangdan (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
Herein, we design a smart autonomous ATP self-powered strand-displacement cascade amplification (SDCA) system for highly sensitive multiple intracellular miRNA detection. Rationally engineered Y-motif DNA structures are functionalized on mesoporous silica-coated copper sulfide nanoparticles loaded with numerous ATPs (CuS@mSiO(2)-Y/ATP) through pH stimulus-responsive disulfide bonds. The SDCA system is implemented by endogenous specific miRNA as a trigger and ATP as fuel released from the nanocarrier at acidic pH and photothermal stimuli-responsive CuS. The ATP self-powered SDCA process presents higher sensitivity compared to that without amplification for intracellular miRNA imaging. Two-color simultaneous and sensitive imaging of multiple cancer-related miRNAs in living cells is also confirmed. This enables facile and accurate differentiation between normal cells and different types of cancer cell using intracellular miRNA imaging, which improves the veracity and timeliness for early cancer diagnosis.